ANDROID-BASED RICE SEED PROCUREMENT APPLICATION DESIGN AND DEVELOPMENT - Fahreza Ghalbi Sekhan; Hajar Puji Sejati (Djtechno: Jurnal Teknologi Informasi, 2024)
Agriculture is the backbone of Indonesia's economy, yet many traditional processes hinder efficiency, particularly in seed distribution. This research aims to develop an online seed ordering application to simplify the process for farmers, enabling them to acquire seeds more quickly and efficiently. The case study was conducted at Berkah Tani Seedling in Temanggung, where the need for a digital solution is urgent. The developed application provides real-time information on seed availability, prices, and delivery, allowing farmers to place orders and make payments online. The implementation results demonstrate that the application reduces the time and costs farmers spend on obtaining seeds, allowing them to focus more on farming activities, and improves inventory management for seed providers. The adoption of this technology not only streamlines the seed distribution process but also significantly enhances the quality of agricultural output. This application is expected to be implemented in other regions to support sustainable agricultural development across Indonesia.